Peran Inovasi Teknologi Hijau dalam Memediasi Pengaruh Green Policy terhadap Kebijakan Ekonomi Nasional yang Berkelanjutan - Harahap, Hastuti Handayani; Rajagukguk, Frederick Rudy Sentosa; Arifin, Indra Welly; Dinata, Randy; Rabiula, Hafizh; Murniati, Neni (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2025)
This study aims to analyze the role of green technology innovation in mediating the influence of green policy on sustainable national economic policy. A quantitative approach was employed using Structural Equation Modeling (SEM) with Partial Least Square (PLS) analysis. Data were collected through surveys of 120 respondents from strategic sectors involved in environmental and economic policymaking. The results reveal that green technology innovation significantly influences both green policy and national economic policy. However, green policy does not directly affect economic policy and does not serve as a significant mediator. These findings imply that green technology innovation has a more substantial direct impact on economic policy than green policy itself. Therefore, strengthening the role of green policy is essential to support sustainable economic development effectively.